Rapid Release Polymeric Fibers for Inhibition of Porphyromonas gingivalis Adherence to Streptococcus gordonii - Mahmoud, Mohamed Y.; Sapare, Sonali; Curry, Keegan C.; Demuth, Donald R.; Steinbach-Rankins, Jill M. (Frontiers in Chemistry, 2020)
Active agents targeting key bacterial interactions that initiate biofilm formation in the oral cavity, may alter periodontitis progression; however, to date, specifically-targeted prophylactic and treatment strategies have been limited. Previously we developed a peptide, BAR (SspB Adherence Region), that inhibits oral P. gingivalis/S. gordonii biofilm formation in vitro and in vivo, and BAR nanoparticles that increase BAR effectiveness via multivalency and prolonged delivery. However, limited BAR loading and nanoparticle retention in the oral cavity can result in inadequate release and efficaciousness. Given this, an effective delivery platform that can release concentrations of BAR suitable for twice-daily applications, may offer an alternative that enhances loading, ease of administration, and retention in the oral cavity. With this in mind, the study objectives were to develop and characterize a rapid-release platform, composed of polymeric electrospun fibers (EFs) that encapsulate BAR, and to evaluate fiber safety and functionality against P. gingivalis/S. gordonii biofilms in vitro. Poly(lactic-co-glycolic acid) (PLGA), poly(L-lactic acid) (PLLA), and polycaprolactone (PCL) were electrospun alone or blended with polyethylene oxide (PEO), to provide high BAR loading and rapid-release. The most promising formulation, 10:90 PLGA:PEO EFs, provided 95% BAR release after 4 hr, dose-dependent inhibition of biofilm formation (IC50 = 1.3 µM), disruption of established dual-species biofilms (IC50 = 2 µM), and maintained high cell viability. These results suggest that BAR-incorporated EFs may provide a safe and specifically-targeted rapid-release platform to inhibit and disrupt dual-species biofilms, that we envision may be applied twice-daily to exert prophylactic effect in the oral cavity.